Benteng Kota Mas di Gorontalo Utara dalam Jaringan Perniagaan di Wilayah Perairan Sulawesi Abad 17-19 M - Irna Saptaningrum; Hasanuddin Anwar; Vivi Sandra Sari; Wuri Handoko (Tumotowa, 2021)
Fort Kota Mas is located in Moluo hamlet, Cisadane village, Kwandang district, North Gorontalo Regency, Gorontalo Province. This colonial heritage building is no longer intact. Some parts have collapsed, leaving some fences, gates, and a bastion behind. Kwandang during 17-19 AD was a strategic trading route and was related to the location of the fort Kota Mas itself. This paper discusses the existence of the fort Kota Mas regarding the hegemony of colonial political power against the local government to the community, as well as its strategic role in the context of commercial shipping lanes in Celebes Sea. This research used descriptive analysis with a historical archaeological perspective. The analysis was carried out based on data collection and on related literature sources. Based on the research results, Fort Kota Mas is an evidence of a hegemony or a domination of colonial control, reflected on several regulations regarding the determination of the value or price of gold and the obligation of local authorities to deposit gold. The strategic role of the fort was as a meeting point (rendezvous) for maritim trade and rivers which developed into trading ports and markets.